Landasan Sosiokultural dalam Pengembangan Kurikulum PAI pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti Sekolah Dasar - Munawar, Fuad; Asep Nursobah (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
Islamic Religious Education (PAI) in elementary schools plays a crucial role in shaping students' moral and spiritual character, especially in a country like Indonesia, which is rich in cultural and religious diversity. This study aims to explore the sociocultural foundations in the development of the PAI curriculum for the PAI and Character Education subjects in elementary schools. This research employs a qualitative approach with a literature review method, where data is collected from 4th-grade PAI textbooks and relevant academic journals. The research design focuses on analyzing literature relevant to curriculum development, emphasizing the selection of data that supports the application of sociocultural values in education. The key findings indicate that integrating sociocultural approaches into the PAI curriculum not only enriches students' understanding of religious values but also strengthens their cultural identity. The implications of this study highlight the importance of reflective and collaborative approaches in teaching, as well as self-assessment-based evaluations to enhance students' honesty and discipline.